2010
DOI: 10.1111/j.1440-1789.2010.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic neural stem cell transplantation increases subventricular zone cell proliferation and promotes peri‐infarct angiogenesis after focal cerebral ischemia

Abstract: Neurogenesis and angiogenesis are two important processes that may contribute to the repair of brain injury after stroke. This study was designed to investigate whether transplantation of human embryonic neural stem cells (NSCs) into cortical peri-infarction 24h after ischemia effects cell proliferation in the subventricular zone (SVZ) and angiogenesis in the peri-infarct zone. NSCs were prepared from embryonic human brains at 8 weeks gestation. Focal cerebral ischemia was induced by permanent occlusion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 49 publications
(107 reference statements)
4
61
0
Order By: Relevance
“…These results prompt further study of HIF, especially given HIF's role in inducing the expression of various previously discussed factors, including VEGF, EPO, and HB-EGF. Transplanted NPCs have also been shown to promote endogenous NPC proliferation in the SVZ [150,151] , angiogenesis [151] , and to release various trophic factors to promote axonal and dendritic plasticity [152] . The latter study found that the predominantly released factor was VEGF, which may explain the proliferative and angiogenic effects.…”
Section: Combinatorial Aproaches To Enhance Stroke Recoverymentioning
confidence: 99%
“…These results prompt further study of HIF, especially given HIF's role in inducing the expression of various previously discussed factors, including VEGF, EPO, and HB-EGF. Transplanted NPCs have also been shown to promote endogenous NPC proliferation in the SVZ [150,151] , angiogenesis [151] , and to release various trophic factors to promote axonal and dendritic plasticity [152] . The latter study found that the predominantly released factor was VEGF, which may explain the proliferative and angiogenic effects.…”
Section: Combinatorial Aproaches To Enhance Stroke Recoverymentioning
confidence: 99%
“…In addition, this transplanted NSCs managed to survive, migrate, differentiate, and also induce improvement in neurological functions (Zhang et al, 2009a(Zhang et al, , 2009bZhang et al, 2010). Grafted NSCs enhanced the number of BrdU-positive cells in ischemic ipsilateral SVZ at 7 days after transplantation, an effect that persisted to at least 14 days post-transplantation.…”
Section: From Theory To Practice: Nscs Transplant In Rodent Models Ofmentioning
confidence: 85%
“…Early research also included undifferentiated pluripotent stem cells, however, their use has become limited due to the risk of teratoma and tumor formation (Kawai et al, 2010;Yamashita et al, 2011). Transplanted cells have been demonstrated to promote stroke recovery in animal models through a variety of mechanisms: stimulating both endogenous NPCs and endothelial progenitor cells to migrate to ischemic sites (Bliss et al, 2010;Lindvall and Kokaia, 2011;Dailey et al, 2013), stimulating the proliferation of neuroblasts in the SVZ (Chen et al, 2003;Jin et al, 2011a;Zhang et al, 2011), promoting angiogenesis in the peri-infarct zone (Horie et al, 2011;Zhang et al, 2011;Oki et al, 2012), and decreasing infarct size (Chen et al, 2010a;Gomi et al, 2012;Oki et al, 2012). In addition to the effects on endogenous tissue, transplanted cells can integrate into the existing neural circuitry, reestablishing connections with host cells ; however, it remains unclear if these new connections contribute directly to recovery.…”
Section: Cell Delivery Goals Of Cell Therapymentioning
confidence: 99%